The Relationship between Smoking and Physical Activity with Cognitive Impairment among the Elderly - Rukia Riskita Dewi Harahap; Rika Sabri; Mahathir Mahathir (GLOBAL HEALTH SCIENCE GROUP, 2025)
The rising number of elderly individuals presents challenges, especially concerning their health and well-being. Without proper intervention, these issues can escalate into more complex problems, including cognitive impairment. To minimize the risk of cognitive impairment that can lead to dementia, it's crucial to reduce risk factors like quitting smoking and engaging in regular physical activity. This study aimed to explore the relationship between smoking, physical activity, and cognitive impairment in the elderly. A retrospective research method was employed, utilizing simple random sampling. The study included 142 elderly participants who met the inclusion criteria. To assess cognitive levels, the Mini Mental State Examination (MMSE) was used. This instrument demonstrated strong validity and reliability, with a Cronbach's Alpha of α=0.827. For measuring physical activity, the Physical Activities Scale For the Elderly (PASE) instrument was utilized, also showing good validity and reliability with a Cronbach's Alpha of α=0.768. Data analysis was conducted using the chi-square statistical test, which revealed a significant relationship between smoking, physical activity, and cognitive impairment in the elderly (p < 0.05). The research findings indicated that the majority of respondents (57.04%) experienced mild cognitive impairment. Additionally, 54.23% of respondents had a history of smoking, and 65.49% exhibited poor physical activity.